(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study, titled "Assessment of Socio-Cultural Factors Influencing Food Security in Uromi, Esan-North-East Local Government of Edo State," aims to investigate the impact of socio-economic, environmental, and infrastructural factors on food security in Uromi, Esan-North-East Local Government of Edo State. The specific objectives include assessing the influence of socio-economic factors, examining environmental impacts on agricultural production, analyzing the role of infrastructure and government policies on food accessibility, and proposing strategies to enhance food security. Using a quantitative research approach, structured questionnaires were administered to 298 respondents selected through simple random sampling. The results indicate that while a significant proportion of households report stable income (Mean = 3.41) and strong social support (Mean = 3.60), considerable challenges remain in accessing nutritious food (Mean = 3.10) and viable employment opportunities (Mean = 2.85). Environmental analysis confirms that soil quality (Mean = 3.38) is a major concern, though water access (Mean = 2.67) is less critical. Critically, infrastructure and policy dimensions reveal severe deficits in storage facilities (Mean = 2.66) and ineffective government programs (Mean = 2.97). However, there is strong community support for sustainable practices (Mean = 3.47) and cooperative farming (Mean = 3.41) as viable solutions. The study concludes that enhancing food security in Uromi requires an integrated strategy combining investment in storage and transport infrastructure, effective policy implementation, promotion of sustainable agriculture, and strengthening of local cooperatives to build a resilient and self-sufficient food system.